Hybrid closed‐loop glucose control with faster insulin aspart compared with standard insulin aspart in adults with type 1 diabetes: A double‐blind, multicentre, multinational, randomized, crossover study. Issue 6 (8th March 2021) - Boughton, Charlotte K.; Hartnell, Sara; Thabit, Hood; Poettler, Tina; Herzig, David; Wilinska, Malgorzata E.; Ashcroft, Nicole L.; Sibayan, Judy; Cohen, Nathan; Calhoun, Peter; Bally, Lia; Mader, Julia K.; et al.
Abstract: Aim: To evaluate the use of hybrid closed‐loop glucose control with faster‐acting insulin aspart (Fiasp) in adults with type 1 diabetes (T1D). Research Design and Methods: In a double‐blind, multinational, randomized, crossover study, 25 adults with T1D using insulin pump therapy (mean ± SD, age 38 ± 9 years, HbA1c 7.4% ± 0.8% [57 ± 8 mmol/mol]) underwent two 8‐week periods of unrestricted living comparing hybrid closed‐loop with Fiasp and hybrid closed‐loop with standard insulin aspart in random order. During both interventions the CamAPS FX closed‐loop system incorporating the Cambridge model predictive control algorithm was used. Results: In an intention‐to‐treat analysis, the proportion of time sensor glucose was in the target range (3.9–10.0 mmol/L; primary endpoint) was not different between interventions (75% ± 8% vs. 75% ± 8% for hybrid closed‐loop with Fiasp vs. hybrid closed‐loop with standard insulin aspart; mean‐adjusted difference −0.6% [95% CI −1.8% to 0.7%]; p < .001 for non‐inferiority [non‐inferiority margin 5%]). The proportion of time with sensor glucose less than 3.9 mmol/L (median [IQR] 2.4% [1.2%–3.2%] vs. 2.9% [1.7%–4.0%]; p = .01) and less than 3.0 mmol/L (median [IQR] 0.4% [0.2%–0.7%] vs. 0.7% [0.2%–0.9%]; p = .03) was reduced with Fiasp versus standard insulin aspart. There was no difference in mean glucose (8.1 ± 0.8 vs. 8.0 ± 0.8 mmol/L; p = .13) or glucose variability (SD of sensor glucose 2.9 ± 0.5 vs. 2.9 ± 0.5 mmol/L; p = .90). Total daily insulin requirements did not differ (49 ± 15 vs. 49 ± 15 units/day; p = .45). No severe hypoglycaemia or ketoacidosis occurred. Conclusions: The use of Fiasp in the CamAPS FX closed‐loop system may reduce hypoglycaemia without compromising glucose control compared with standard insulin aspart in adults with T1D.